Democracy and human rights (RGICS project ;, 1995)
Contributed articles presented at the Conference on "Democracy and Human Rights" held from 11-13 Jan. 1995, organized by Rajiv Gandhi Institute for Contemporary Studies; with special reference to India and Britain.